Essays on Health Economics - SILVA, Lucas Emanuel da (2019)
This thesis encompasses two chapters that empirically analyze the effects of positive and negative in utero events on birth outcomes in Brazil. Both issues are related to Health Economics literature. Below are the abstracts for the respective chapters. Chapter 1. Water and Birth Weight: Evidence from a large scale program in the Brazilian Semiarid Region. This paper studies how in utero exposure to a large-size water harvesting program affects birth outcomes. We assess the effects of the Cisterns Program, which built approximately one million cisterns in Brazil’s poorest and driest region to promote small-scale decentralized rainfall harvesting and storage. Our empirical strategy compares the outcomes of women exposed to cisterns in different stages of their pregnancy. The results show that access to cisterns during early pregnancy increases birth weight, particularly for more educated women. The results suggest that policies for adaptation and reduction of vulnerability may bring about positive effects on an important predictor of future individual outcomes. Chapter 2. Environmental disasters and infant health: Evidence from the Mariana mining disaster in Brazil. Implementation and enforcement of environmental regulation policies are necessary for promoting environmentally sustainable industrial development. When such policies are poorly enforced, there is a chance significant impact on the local communities. We study the health consequences of one of the largest environmental disasters in the global mining industry, which largely stemmed from regulatory failure. Taking advantage of the timing and location of the Mariana mine tailings dam collapse in Brazil, we show that in utero exposure to the tragedy significantly reduced birth weight and increased infant mortality. The adverse effects were stronger for infants born to less educated and single mothers. These findings indicate that poorly enforced environmental regulation may have long-term welfare impacts on local communities.